Developmental trends in Setswana literature - Seekoe, Phokwane Wilhelminah (University of the Free State (South Campus), 1998)
A Marxist literary theory is used in this study. The aim of this study is to evaluate some Setswana novels using a developmental approach. The time frame of this study will extend from the time the missionaries came to South Africa until 1994. Karl Marx's background has been discussed. The following Marxist models are explained, i.e. reflection model, production model, genetic model, negative knowledge model and language centred models. An explanation of some Marxist concepts, e.g. ideology, dialectic, base, superstructure, reification and alienation have been given (Chapter 1). Three Marxist models are used, namely reflection, production and genetic. These models are used in the discussion of Mokwena. Rammone wa Kgalagadi and Motimedi. The study highlights how missionaries manipulated Setswana literary creativity in an attempt to promote Christianity and how some Setswana authors resisted the attempt to make Setswana literature instruments for Christianising people (Chapter 2). The development of the following novels: Sephaphati, Matlhoko, Matlhoko and Masego are discussed. Three Marxist models are utilised in the evaluation of these novels, namely reflection, production and genetic although the Government also harnessed Setswana literary creativity in an attempt to promote their ideology, some Setswana authors nevertheless resisted these attempts by the government (Chapter 3). Explanation of the findings of the aim of the study is given. Mokwena primarily addresses its Christian readers (Batswana). Rammone wa Kgalagadi highlights the traditional world and westernised Christian world. Motimedi focuses on hardships experienced by Blacks, though Christianity also plays a role when the main character is converted. Sephaphati focuses on the Christian world and the westernised world. Matlhoko, Matlhoko highlights the implementation of the segregation acts in South Africa before 1994. Masego focuses on the impact of the oppressive laws of South Africa prior to 1994. The conclusion illustrates how Setswana authors were influenced by their traditional, cultural, religious and socio-economic background in writing the novels that I have evaluated (Chapter 4).
Dissertation (M.A. (African Languages))--University of the Free State, 1998
Keywords: Tswana literature; Tswana literature -- History and criticism; Tswana literature -- Study and teaching